A Critical Review of Foreign Language Interpreter Practices in Indonesian Courts - Attruk, Muhammad Fariq Heemal; Putra, Rizky Perdana Bayu; Handayani, Tuti (Universitas Kristen Cipta Wacana, 2025)
This paper presents a critical investigation into the use of foreign language interpreters in Indonesian courts by integrating insights from applied linguistics and legal scholarship. The primary goal is to assess current translation practices, identify the systemic barriers to accuracy, and propose actionable strategies for reform. Using the Critical Literature Review (CLR) approach, the study draws from scholarly sources indexed in Scopus, GARUDA, and Google Scholar, focusing on literature published between 2015 and 2025. The review identifies a number of recurring issues, including the overreliance on unaccredited ad hoc interpreters, recurring errors in rendering legal terminology, and undue influence from courtroom actors, all of which undermine interpreter neutrality. These problems often result in significant legal ramifications such as nullified legal documents, flawed judicial decisions, and the infringement of defendants’ rights. Additionally, the absence of standardized interpreter training and certification, combined with uneven policy implementation across regions, further complicates the situation. In response, the study recommends solutions such as realistic courtroom simulations for interpreter training, the adoption of digital tools like bilingual legal term databases, and interdisciplinary cooperation to formulate inclusive and rights-focused translation standards. Policy-level interventions are also suggested, including the revision of Supreme Court Circular No. 3/2023 and the incorporation of globally recognized best practices. While offering important contributions, the study also notes limitations, particularly in terms of regional representativeness and the underexplored role of AI in legal translation. Ultimately, the findings reinforce the importance of bridging linguistic expertise and legal frameworks to strengthen translation quality and promote equitable access to justice in Indonesia’s legal system.